Reproductive potential and growth of Stolephorus bataviensis from Dakshina Kannada coast - Doddamani, M; Ramesha, T J; Laxmipathi, M T; Annappaswamy, T S; Shanbhogue, S L (Indian Journal of Fisheries, 2011)
The reproductive potential and growth aspects of Stolephorus bataviensis havebeen studied. The fish showed intermittent spawning throughout the year withpeak activity during March-May. Males appear to mature earlier than females.The fecundity ranged from 898 to 2436 eggs per individual. Life span of S.bataviensis was found to be 1.53 years and the Von Bertallanffy growth equationwas Lt=11.77 (l-e-0.1629(t+0.0540)).